Pengaruh Experiential Marketing Terhadap Customer Satisfaction dan Repurchase Intention Pada Layanan Grabfood Selama Pandemi Covid-19 - Tuqa, Bimo Rana; Widyastuti, Hardiana (Institut Pertanian Bogor, 2022)
The Indonesian government has issued a policy of Enforcement of Community Activity Restrictions (PPKM) to overcome the problem of the pandemic. Ordering food online is the largest monthly consumer digital expenditure during the COVID-19 pandemic. Gross Merchandise Value (GMV) of food delivery services in Indonesia is US 3.7 billion. Grabfood contributed 1.96 billion USD or 53% of Indonesia's total GMV. The purpose of this study was to analyze the effect of experimental marketing on customer satisfaction and repurchase intention, as well as the effect of customer satisfaction on repurchase intention on Grabfood services during the Covid-19 pandemic. The purpose of this study is to analyze the effect of experimental marketing on customer satisfaction and repurchase intention, as well as the effect of customer satisfaction on repurchase intention on Grabfood services during the Covid-19 pandemic. In this study, the sampling technique used was non-probability sampling with aapproach judgmental sampling with a total sample of 190 samples. The data analysis technique used is descriptive analysis approach and SEM-PLS analysis. The results of this study indicate that experimental marketing has a positive and significant effect on customer satisfaction and repurchase intention and customer satisfaction has a positive and significant influence on repurchase intention on Grabfood services during the Covid-19 pandemic.